Dampak Pemberian Fasilitas Fiskal terhadap Iklim Bisnis di Kabupaten Pasuruan: Studi Empiris di Wilayah Pengawasan Bea Cukai Pasuruan - Nuh Bachrudin Rizqi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the implementation of fiscal facilities for business actors in Pasuruan Regency, measure their contribution to the regional business climate, and evaluate the outcomes of such fiscal incentives on economic growth, particularly the Gross Regional Domestic Product (GRDP) of Pasuruan Regency. The research employs a quantitative method with a descriptive approach. In 2024, foreign exchange earnings from export activities within the Bonded Zone in Pasuruan Regency reached IDR 31.54 trillion, while the region’s GRDP amounted to IDR 201.67 trillion, indicating a significant contribution of the export sector to the local economy. The results of this study are expected to provide an objective overview of the effectiveness of fiscal facilities and serve as a basis for formulating more targeted and sustainable regional economic development policies.